2023
DOI: 10.3389/fchem.2023.1167783
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron production of 43Sc and 44gSc from enriched 42CaO, 43CaO, and 44CaO targets

Abstract: Introduction:43Sc and 44gSc are both positron-emitting radioisotopes of scandium with suitable half-lives and favorable positron energies for clinical positron emission tomography (PET) imaging. Irradiation of isotopically enriched calcium targets has higher cross sections compared to titanium targets and higher radionuclidic purity and cross sections than natural calcium targets for reaction routes possible on small cyclotrons capable of accelerating protons and deuterons.Methods: In this work, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…The production of 45 Ti and 44 Sc has been described previously. Briefly, for 45 Ti, metal disks of nat Sc (9.5 mm diameter and 0.24 mm thickness) were spot-welded to tantalum backing coins (22 mm diameter and 1 mm thickness) and introduced to the proton beam of the University of Wisconsin’s General Electric PETtrace cyclotron using the GE Solid Target Platform, degraded to 11.8 MeV by passing through a 0.5 mm aluminum foil. After irradiation, activated nat Sc containing 45 Ti was dissolved in 5 mL of 6 M HCl, diluted to 15 mL with 18 MΩ-cm H 2 O, and loaded onto a preequilibrated ZR-resin (Triskem, France, preconditioned with 10 mL H 2 O and 2-5 mL 2M HCl) column.…”
Section: Resultsmentioning
confidence: 99%
“…The production of 45 Ti and 44 Sc has been described previously. Briefly, for 45 Ti, metal disks of nat Sc (9.5 mm diameter and 0.24 mm thickness) were spot-welded to tantalum backing coins (22 mm diameter and 1 mm thickness) and introduced to the proton beam of the University of Wisconsin’s General Electric PETtrace cyclotron using the GE Solid Target Platform, degraded to 11.8 MeV by passing through a 0.5 mm aluminum foil. After irradiation, activated nat Sc containing 45 Ti was dissolved in 5 mL of 6 M HCl, diluted to 15 mL with 18 MΩ-cm H 2 O, and loaded onto a preequilibrated ZR-resin (Triskem, France, preconditioned with 10 mL H 2 O and 2-5 mL 2M HCl) column.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have described nuclear reactions under different conditions for the production of Sc-43 and Sc-44 from calcium and titanium, with different outcomes in each case, in terms of the yields and purities of the various radionuclides produced [ 43 , 58 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. These scandium isotopes can be produced via multiple routes.…”
Section: Properties and Effects Of Scandium In The Context Of Nuclear...mentioning
confidence: 99%
“…In this context, many studies have been reported for the nuclear reactions under different conditions for production of Sc-47, exhibiting different results in terms of yields and radionuclide purities ( Table 2 ) [ 43 , 59 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. In contrast to Sc-43 and Sc-44, the production of Sc-47 can proceed by using high-energy proton irradiation of titanium [ 104 ], calcium [ 105 , 106 ], and vanadium targets [ 100 , 107 , 108 , 109 ].…”
Section: Properties and Effects Of Scandium In The Context Of Nuclear...mentioning
confidence: 99%
See 1 more Smart Citation